[Kartka z kalendarza podziemnego na Listopad 1984] . Card from an unofficial calendar for November 1984 (Polska, 1984)
Double-sided, brown print on white paper. The front of the page contains a listing of events that happened in November. The back of the page contains a citation from the Bible (Numbers, 35:33).